2016
DOI: 10.1590/1981.81222016000300004
|View full text |Cite
|
Sign up to set email alerts
|

Mulher e mercado: participação e conhecimentos femininos na inserção de novas espécies de pescado no mercado e na dieta alimentar dos pescadores da RESEX Mãe Grande em Curuçá (PA)

Abstract: Resumo: O artigo descreve como o conhecimento tradicional da mulher marisqueira e pescadora de rio e mar, da localidade de Caratateua, RESEX Marinha Mãe Grande de Curuçá (PA), contribui na inserção e comercialização de novas espécies de pescado. O trabalho utiliza metodologia quali-quantitativa e produz dados que apontam para um quadro de escassez dos pescados mais apreciados no mercado local. Apresenta o conhecimento tradicional feminino sobre as espécies-chave que compõem a dieta dos pescadores, sendo esse u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(5 reference statements)
0
3
0
5
Order By: Relevance
“…In spite of that, it is observed that the woman has an expressive participation because carries out the work in an equalitarian way to the men. Scenery different to the that is found in other fishing modalities in Brazil and in the Amazonian where happens the division of gender of the work (Fonseca et al, 2016;Palheta et al, 2016). A lot of times the woman doesn't participate directly of the activities, being that exclusive to the men and the women fits the children's cares and the accomplishment of the daily domestic services (Santana, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…In spite of that, it is observed that the woman has an expressive participation because carries out the work in an equalitarian way to the men. Scenery different to the that is found in other fishing modalities in Brazil and in the Amazonian where happens the division of gender of the work (Fonseca et al, 2016;Palheta et al, 2016). A lot of times the woman doesn't participate directly of the activities, being that exclusive to the men and the women fits the children's cares and the accomplishment of the daily domestic services (Santana, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Na mesma o motivo de estas extrativistas terem se tornado membro da referida associação foi a falta de oportunidade de emprego formal ou para obter um complemento de rendimentos. Deste modo, as marisqueiras encontram nos recursos dos ecossistemas pesqueiros um meio de obtenção de renda e complemento do sustento familiar, assim como participam de organizações sociais em busca de seus direitos e reconhecimento perante a sociedade (MANESCHY, 2000;PALHETA et al, 2016).…”
Section: Resultados/discussõesunclassified
“…Estas mulheres, em sua maioria, alegaram que estão afiliadas à associação da classe desde o seu período de fundação, isto é, há 17 anos (50,0%) (Figura 1). Neste contexto, frisase a importância de haver um órgão da categoria in loco, pois, de acordo com Freitas et al No mais, é fato que as atividades femininas na pesca, como a mariscagem, estão à revelia de sua importância ou são consideradas inferiores ou tem a invisibilidade de suas atividades devido ao modelo patriarcal de relações sociais, como já verificado no município de Curuçá (PALHETA et al, 2016). Da mesma forma, ainda hoje o espaço social que as marisqueiras ocupam tem permanecido invisível por grande parte dos pesquisadores e, principalmente, pelos poderes públicos em todas as esferas administrativas (DIAS et al, 2007).…”
Section: Resultados/discussõesunclassified
“…Added to the influence of climatic factors and oceanographic conditions, it was noted that a tendency towards decreased stock was also observed in Pará, from comparison of CPUE over the years, although without any statistically significant reduction (Leão et al 2019). In the northern and northeastern regions, several studies have been suggesting that there is a risk of overexploitation of S. brasiliensis (Lessa et al 2004, Isaac-Nahum 2006, Lessa 2006, Almeida et al 2007, Espírito-Santo & Isaac 2012, Palheta et al 2016, Leão et al 2019. In the southern region, ).…”
Section: Discussionmentioning
confidence: 99%